Current Trends on Role of Biological Treatment in Integrated Treatment Technologies of Textile Wastewater - Ceretta, Maria Belen; Nercessian, Débora; Wolski, Erika A. (Frontiers in Microbiology, 2021)
Wastewater discharge is a matter of concern as it is theprimary source of water pollution.Consequently, wastewater treatment plays a keyrole in reducing thenegative impactthat wastewater discharge produce into theenvironment.Particularly, theeffluents produced by textile industry are composed of high concentration ofhazardous compounds such as dyes, as well as having high levels of chemical and biological oxygen demand,suspended solids,variable pH,and high concentration of salt.Main efforts have been focused on the development of methods consuming less water or reusing it,and also onthe development of dyes with a better fixation capacity.However, the problem of how to treat these harmful effluents isstill pending.Differenttreatment technologies have been developed, suchas coagulation, adsorption,filtration, reverse osmosis, advancedoxidation andbiological processes.Concerning to biological treatments,even though they are considered as the most environmentallyfriendly and economic methods,their industrial application is still uncertain.This is due to the costs of treatment plants installation and,to the fact that mostof thestudies are carried out with simulated or diluted effluents that do not represent what really happens in the industries.Integrated treatment technologies by combining the efficiency two or more methodologies used to be more efficient for the decontamination of textile wastewater, thantreatments used separately.The elimination of hazardous compounds had been reported using combination of different processes.As degradation products can sometimes be even moretoxic than the parentcompounds, effluenttoxicity assessment is an essential featur.This article provides a critical view onthe state ofart of biological treatment, the degree of advancement and the prospects for their application,also discussingthe concept ofintegrated treatment and the importanceof including toxicityassays toreach an integralapproach to wastewater treatment.